THE EFFECT OF HONEY PINEAPPLE JUICE (Ananas conosus var. cayenne) ON DISCOLORATION OF COMPOSITE RESIN DUE TO COFFEE IMMERSION - Saskya Aldina Nur Amalina; Nadia Hardini; Lusiana Batubara; Brigitta Natania Renata Purnomo (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Discoloration of the composite resin can be cleaned using chemicals. However, chemicals are still being debated because they have some side effects. This has led researchers to look for natural materials that can be used to clean composite resins. Honey pineapple contains organic acids and the enzyme bromelain which can be used to clean teeth. Objectives: This study aims to determine the effect of honey pineapple juice on the color change of composite resin due to coffee immersion after soaking honey pineapple juice for 1, 3, and 5 days. Methods: This type of research is an experimental laboratory with a pre test - post test group design. The research data were tested using paired t test and one way ANOVA test. Results: The results showed that there were differences in the color change of the composite resin due to coffee immersion after soaking honey pineapple juice for 1, 3, and 5 days. Conclusions: There is an effect of honey pineapple juice on the color change of the composite resin due to coffee immersion and there are differences in the color change of the composite resin due to coffee immersion after soaking honey pineapple juice for 1, 3, and 5 days. The highest color change occurred in immersion for 5 days. Keywords: Coffee Immersion, Discoloration of composite resin, Honey pineapple juice